Targeted Next-Generation Sequencing of Korean Patients With Developmental Delay and/or Intellectual Disability - Han, Ji Yoon; Jang, Ja Hyun; Park, Joonhong; Lee, In Goo (Frontiers in Pediatrics, 2018)
Background: Differential diagnosis of developmental delay (DD) and/or intellectual disability (ID) is challenging because of the diversity of phenotypic manifestations as DD/ID patients usually have combined congenital malformations, autism-spectrum disorders, and/or seizure disorder. Thus, unbiased genomic approaches are needed to discover genetic alterations leading to DD and/or ID Objective: The aim of this study was to investigate the clinical usefulness of targeted next-generation sequencing (NGS) to investigate genetic causes in 35 Korean patients with unexplained DD/ID. Methods: Targeted next-generation sequencing (NGS) using the TruSight One Panel was analysed in 35 patients with unexplained DD/ID. Sanger sequencing was used to confirm candidate variants, and to define genetic inheritance mode of candidate variant as familial segregation testing. Results: Of 35 patients with DD and/or ID, 10 were found to have underlying genetic aetiology and carried X-linked recessive inheritance of ZDHHC9 or autosomal dominant inheritance of SMARCB1, CHD8, LAMA5, NSD1, PAX6, CACNA1H, MBD5, FOXP1, or KCNK18 mutations. No autosomal recessive inherited mutation was identified in this study. As a result, the diagnostic yield of DD/ID by targeted NGS was 29% (10/35), mostly involving may be de novo mutation present in the proband only. A total of seven may be de novo mutations, one paternally inherited, and one maternally inherited mutations that had been reported previously to concede the genetic pathogenesis as known DD and/or ID genes were found in nine patients with available inheritance pattern except LAMA5. Mutations in nine causative genes were detected in patients with similar DD/ID phenotypes in the OMIM database, providing support for genetic evidence as the cause of DD and/or ID. Conclusion: Targeted NGS through singleton analysis with phenotype-first approaches was able to explain 10 out of 35 DD/ID cases. However, the excavation of plausible genetic causes may be de novo, and X-linked disease-causative variants in DD/ID-associated genes requires further genetic analysis.